USABILITY ANALYSIS OF VISUAL NOVEL GAMES USING THE USABILITY TESTING METHOD - Kurniawan Adi Perdana (INSTEP Network, 2022)
Visual novel games are interactive fiction games featuring static images. Visual novel games focus on the story of one of the visual novel games that game lovers often play, namely the game The Sun Shine Over Us. This game tells about mental health among teenagers. The purpose of this research is to analyze the “The Sun Shine Over Us” game based on several criteria and the satisfaction of using the application by users. This study uses the system usability scale method to determine the level of satisfaction of this visual novel game player. The data used are players who have played and have never played a visual novel game totaling 17 people with the age category of 17-28 years. Based on the reviews from players who have played visual novel games, the results of this study can be concluded that the visual game